2011
DOI: 10.1530/joe-11-0017
|View full text |Cite
|
Sign up to set email alerts
|

5′AMP-activated protein kinase activity is increased in adipose tissue of northern elephant seal pups during prolonged fasting-induced insulin resistance

Abstract: Northern elephant seals endure a 2–3 month fast characterized by sustained hyperglycemia, hypoinsulinemia and increased plasma cortisol and free fatty acids, conditions often seen in insulin resistant humans. We previously showed that adipose Glut4 expression and AMP kinase (AMPK) activity increase and plasma glucose decreases in fasting seals suggesting that AMPK activity contributes to glucose regulation during insulin resistant conditions. To address the hypothesis that AMPK activity increases during fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(128 citation statements)
references
References 49 publications
10
116
2
Order By: Relevance
“…While activation of systemic RAS may result from food deprivation to help regulate osmotic homeostasis (Ortiz et al, 2000;Ortiz et al, 2002;Ortiz et al, 2006), the effects of this increase in RAS on cellular functions in seals have not been examined. Given that these animals present with an IR-like condition during prolonged fasting (Fowler et al, 2008;Viscarra et al, 2011a;Viscarra et al, 2011b), this study suggests that the activation of systemic RAS, not local RAS, is most likely contributing to the IRlike condition observed in fasting seal pups. In humans and rodents, excess TNF-α in muscle can disrupt the tyrosine-phosphorylation of IRS (Plomgaard et al, 2005) and suppress fatty acid oxidation by suppressing AMPK signaling (Steinberg et al, 2006), which can contribute to impaired wholebody insulin sensitivity because muscle is responsible for the majority of glucose uptake in vivo.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…While activation of systemic RAS may result from food deprivation to help regulate osmotic homeostasis (Ortiz et al, 2000;Ortiz et al, 2002;Ortiz et al, 2006), the effects of this increase in RAS on cellular functions in seals have not been examined. Given that these animals present with an IR-like condition during prolonged fasting (Fowler et al, 2008;Viscarra et al, 2011a;Viscarra et al, 2011b), this study suggests that the activation of systemic RAS, not local RAS, is most likely contributing to the IRlike condition observed in fasting seal pups. In humans and rodents, excess TNF-α in muscle can disrupt the tyrosine-phosphorylation of IRS (Plomgaard et al, 2005) and suppress fatty acid oxidation by suppressing AMPK signaling (Steinberg et al, 2006), which can contribute to impaired wholebody insulin sensitivity because muscle is responsible for the majority of glucose uptake in vivo.…”
Section: Discussionmentioning
confidence: 73%
“…For the maintenance of circulating glucose levels, fasting pups rely on lipid oxidation and efficient glucose recycling (Champagne et al, 2005;Champagne et al, 2012;Costa and Ortiz, 1982;Tavoni et al, 2013), coupled with insulin resistance (IR)-like conditions (Fowler et al, 2008;Viscarra et al, 2011a;Viscarra et al, 2011b). These adapted mechanisms allow pups to meet their energetic burdens during prolonged fasting.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma HGPRT and XO activities increased (P<0.05) at each week across the fasting over the 7week measurement period (Fig.4C,D). cortisol, non-esterified fatty acids and promoting insulin resistance (Ortiz et al, 2000;Ortiz et al, 2001;Ortiz et al, 2003;Ortiz et al, 2006;Vázquez-Medina et al, 2010;Viscarra et al, 2011a;Viscarra et al, 2011b). Unfortunately, the molecular and physiological mechanisms adopted by seals to cope with prolonged fasting are not fully elucidated.…”
Section: Purine Metabolism Increases With Fastingmentioning
confidence: 99%
“…In humans, rats and mice, prolonged fasting increases oxidant production, oxidative damage and inflammation (Crescimanno et al, 1989;Di Simplicio et al, 1997;Grattagliano et al, 2000;Kondoh et al, 2003;Mårtensson, 1986;Sorensen et al, 2006;Souza Rocha et al, 2008;Wu et al, 2004). In elephant seals, prolonged fasting does not induce oxidative damage or inflammation despite promoting the chronic activation of the renin-angiotensin system (RAS) and increasing circulating cortisol, NADPH oxidase activity, Nox4 protein expression and insulin resistance (Ortiz et al, 2000;Ortiz et al, 2002;Vázquez-Medina et al, 2010;Viscarra et al, 2011a;Viscarra et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, males have low rates of water flux and spare protein efficiently (Ortiz et al, 2006;Crocker et al, 2012). Studies in fasting and lactating female elephant seals have suggested reduced insulin response and sensitivity (Fowler et al, 2008;Viscarra et al, 2011aViscarra et al, , 2011b. To date, no studies have examined the hormone regulation of metabolism in adult male pinnipeds during natural breeding fasts.…”
Section: Introductionmentioning
confidence: 99%